2022
DOI: 10.1158/1078-0432.ccr-21-2468
|View full text |Cite
|
Sign up to set email alerts
|

Bias Reduction through Analysis of Competing Events (BRACE) Correction to Address Cancer Treatment Selection Bias in Observational Data

Abstract: Purpose: Cancer treatments can paradoxically appear to reduce the risk of noncancer mortality in observational studies, due to residual confounding. Here we introduce a method, Bias Reduction through Analysis of Competing Events (BRACE), to reduce bias in the presence of residual confounding. Experimental Design: BRACE is a novel method for adjusting for bias from residual confounding in proportional hazards models. Using sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Limitations in our study include its retrospective design and lack of standardized follow-up protocols. Furthermore, the NCDB lacks cause-specific outcomes data which may confound analyses of treatment effects in observational studies [ 40 ]. Importantly, the NCDB lacks data on a well described adverse feature, perineural invasion, as well as other pathologic risk factors such as close margins and other factors associated with survival, including tobacco use status and cumulative lifetime tobacco use, and therefore our analyses were unable to incorporate these potentially important prognostic indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations in our study include its retrospective design and lack of standardized follow-up protocols. Furthermore, the NCDB lacks cause-specific outcomes data which may confound analyses of treatment effects in observational studies [ 40 ]. Importantly, the NCDB lacks data on a well described adverse feature, perineural invasion, as well as other pathologic risk factors such as close margins and other factors associated with survival, including tobacco use status and cumulative lifetime tobacco use, and therefore our analyses were unable to incorporate these potentially important prognostic indicators.…”
Section: Discussionmentioning
confidence: 99%
“…This study was limited by missing data on HPV status and additional key clinical characteristics, such as smoking and performance status, A separate analysis of the SEER-Medicare database similarly suggested that carboplatinbased regimens were not only superior to cetuximab, but were also similar in efficacy to cisplatin [56]. Unfortunately, selection bias is a common problem with retrospective studies in competing risks populations, even after controlling for confounding variables with propensity score models [57]. Collectively, these studies highlight the need to compare alternative treatment regimens in randomized trials.…”
Section: Cytotoxic Radiosensitizersmentioning
confidence: 97%
“…The authors did not describe the technique followed for hemostasis, and we have already demonstrated that the effect of hemostasis depends on the energy of the coagulation devices used compared with conventional hemostasis with knots. 2,3 In addition, an incidence of 8.3% and 2.5%, respectively, in the 2 groups regarding postthyroidectomy hemorrhage could be considered quite high, especially when the procedure is performed by an experienced endocrine surgeon. 4 Furthermore, in the prospective group, the authors decided to include only patients having risk factors for bleeding and they did not report or compare the incidence of postoperative bleeding and the variation of the neck circumference in patients without risk factors.…”
Section: Neck Diameter As a Diagnostic Tool For The Detection Of Post...mentioning
confidence: 99%
“…An observational study comparing cetuximab and cisplatin undoubtedly would have been marred by treatment selection bias and would require bias mitigation techniques such as BRACE. 2 Cetuximab and carboplatin-based treatment, on the other hand, are both considered alternative radiosensitizing approaches in cisplatin-ineligible patients (National Comprehensive Cancer Network category 2B); thus, physicians may regard them as somewhat interchangeable in both efficacy and toxic effects. As seen in the RTOG 1016 clinical trial, 3 however, cetuximab with radiotherapy was associated with some unique toxic effects and is not necessarily "less intensive" compared with carboplatin.…”
mentioning
confidence: 99%